FAKTOR FUNDAMENTAL DAN PENGARUHNYA TERHADAP RETURN SAHAM - Fadil Iskandar (Universitas Batanghari Jambi, 2016)
This research was conducted to find out the fundamental variables influence against return company stock LQ45. As for the fundamental variables examined is financial leverage ratio, dividend payout ratio, and book value per share. The results showed that all the free variables in simultaneous partial or no effect significantly to return stock, because the company's leverage level is still within the limits of reasonableness. Party investors prefer growth companies, with the hope of return in the future will be higher. Investors are also not looking at the low book value as a risk not getting the cash return.Key words: fundamental variables, financial leverage ratio, dividend payout ratio, book value per share, stock return.